Difficulties in teaching and reading vocabulary in the textbook English for food production staff" for the second year students of pre-intermediate level at Hanoi Tourism College - Mai, Tuyet Nhung (University of Languages and International Studies, 2017)
In learning a foreign language, vocabulary is the key to success. Without vocabulary, it is so difficult to convey anything. Thus, to teach vocabulary efficiently to students is the desire of any teachers. In the context of Hanoi Tourism College, teaching (...)